Sviluppo e implementazione di un modello farmacoeconomico per valutare la costo efficacia di un ACE-inibitore nella prevenzione del rischio cardiovascolare - Iannazzo, Sergio; Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2003)
Cardiovascular disease (CVD) remains one of the leading causes of mortality and morbidity worldwide. Since several pharmacological approaches are available for the reduction of incidence and severity of cardiovascular events and health resources in modern managed care systems are limited, the evaluation of the clinical and economical consequences of any treatment is very valuable for decison-makers and physicians. In this article we present a flexible pharmacoeconomic model that permits the calculation of the marginal costeffectiveness of cardiovascular prevention with ramipril, a drug of the class of ACE-inhibitors. The clinical data used for the modelization are derived from the HOPE (Heart Outcomes Prevention Evaluation) study, a landmark cardiovascular prevention study that showed how the benefits of ACE-inhibition with ramipril go beyond the effects on blood pressure, while Italian epidemiological, demographic and economical data make the results appliable to the Italian population. The model, structured as a decision tree comparing the alternatives “to treat” or “not to treat” with Markow chains at the terminal nodes, calculates the marginal cost-effectiveness of the preventive treatment in terms of cost/year of live saved. The model is characterized by high flexibility, as it allows health decision-makers to set epidemiological and economical data in order to reflect the local population at high risk for developing cardiovascular diseas. The model was tested on a high risk population, formed by all acute myocardial infarction survivors in Italy, and indicated that life-long treatment of this patients would yield significant clinical benefits, with a cost/ effectiveness of 3,932 euro/year of life saved. This value is well below the standards that are considered acceptable, and offsprings from the partial offset of pharmaceutical costs caused by the reduction in the expenses for diagnosis and treatment of the cardiovascular events avoided with the preventive therapy.